2000
DOI: 10.1161/01.hyp.35.4.904
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Nitric Oxide and Coronary Risk Factors

Abstract: Abstract-Platelet aggregation is inhibited through a negative feedback mechanism by the L-arginine/nitric oxide (NO) pathway found in platelets themselves. We have shown that long-term smoking impairs the bioactivity of platelet-derived NO (PDNO), resulting in an increased platelet aggregability. However, little is known about the relation between other coronary risk factors and PDNO release. Accordingly, this study was undertaken to examine whether other coronary risk factors are related to the impairment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 24 publications
(26 reference statements)
1
37
0
Order By: Relevance
“…An NO-selective electrode is specifically capable of measuring real-time release of NO from aggregating platelets, 17 and we have previously confirmed that the change in the electrical current obtained by the NO-selective electrode reflects the amount of NO released through the L-arginine/NO pathway in aggregating human platelets. 7 Recently, we demonstrated that the number of coronary risk factors correlates with the degree of an impairment of PDNO release by human platelets, 13 and we had a similar finding in the present study. All these findings suggest that the L-arginine/NO pathway, which is a negative feedback mechanism that inhibits platelet aggregation, is indeed impaired in patients with coronary risk factors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…An NO-selective electrode is specifically capable of measuring real-time release of NO from aggregating platelets, 17 and we have previously confirmed that the change in the electrical current obtained by the NO-selective electrode reflects the amount of NO released through the L-arginine/NO pathway in aggregating human platelets. 7 Recently, we demonstrated that the number of coronary risk factors correlates with the degree of an impairment of PDNO release by human platelets, 13 and we had a similar finding in the present study. All these findings suggest that the L-arginine/NO pathway, which is a negative feedback mechanism that inhibits platelet aggregation, is indeed impaired in patients with coronary risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…7,13,14 The NO meter and electrodes were placed in an electromagnetic shield box to avoid electrical perturbation. The electrodes were placed in the chamber containing the gel-filtered platelets and after the addition of Ca 2+ and fibrinogen, followed by ADP (5 mol/ml), the working electrode was supplied with +0.6 V for electrochemical oxidation of NO.…”
Section: Measurements Of Pdno With An No-specific Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…30,35 Despite controversy, consistent data suggest that platelet-derived NO participates in platelet inhibition and thrombosis prevention and that conditions characterized by defective platelet NO production, such as hypertension or treatment with some antiretroviral drugs, are associated with an enhanced risk of ischemic cardiovascular events. 18,19,36 Recent data showing impaired cGMP formation and enhanced platelet reactivity in patients with myocardial infarction carrying 2 gene mutations affecting soluble guanylyl cyclase function confirm the importance of NO-mediated platelet inhibition in the prevention of thrombosis. 37 Therefore, to clarify the role of platelet-derived NO in the antithrombotic effects of dl-nebivolol, we used chimeric mice.…”
Section: Discussionmentioning
confidence: 97%
“…16 Platelet-derived NO release and endothelium-derived NO-mediated vasodilatation is impaired with conventional cardiovascular risk factors, a fact that supports a link between the L-arginine-NO ·Ϫ pathway in platelets and endothelial cells. 17 We have previously used the platelet as a compartmentalized tissue model to study the interaction of NO and O 2 ·Ϫ and the functional consequences associated with altered platelet reactivity. 11,12 All components of the L-arginine-NO pathway present in endothelial cells are found in platelets, and eNOS protein has been identified in platelets by Western blotting.…”
Section: Discussionmentioning
confidence: 99%